Development and validation of an immune‐related prognostic signature in lung adenocarcinoma. (26th June 2020) - Sun, Sijin; Guo, Wei; Wang, Zhen; Wang, Xin; Zhang, Guochao; Zhang, Hao; Li, Renda; Gao, Yibo; Qiu, Bin; Tan, Fengwei; Gao, Yushun; Xue, Qi; et al.
Abstract: Background: Lung adenocarcinomas (LUAD) is the most common histological subtype of lung cancers. Tumor immune microenvironment (TIME) is involved in tumorigeneses, progressions, and metastases. This study is aimed to develop a robust immune‐related signature of LUAD. Methods: A total of 1774 LUAD cases sourced from public databases were included in this study. Immune scores were calculated through ESTIMATE algorithm and weighted gene co‐expression network analysis (WGCNA) was applied to identify immune‐related genes. Stability selections and Lasso COX regressions were implemented to construct prognostic signatures. Validations and comparisons with other immune‐related signatures were conducted in independent Gene Expression Omnibus (GEO) cohorts. Abundant infiltrated immune cells and pathway enrichment analyses were carried out, respectively, through ImmuCellAI and gene set enrichment analysis (GSEA). Results: In Cancer Genome Atlas (TCGA) LUAD cohorts, immune scores of higher levels were significantly associated with better prognoses ( P < .05). Yellow (n = 270) and Blue (n = 764) colored genes were selected as immune‐related genes, and after univariate Cox regression analysis ( P < .005), a total of 133 genes were screened out for subsequent model constructions. A four‐gene signature (ARNTL2, ECT2, PPIA, and TUBA4A) named IPSLUAD was developed through stability selection and Lasso COX regression. It was suggested by multivariate and subgroup analyses that IPSLUAD was an independent prognostic factor. It was suggested by Kaplan‐Meier survival analysis that eight out of nine patients in high‐risk groups had significantly worse prognoses in validation data sets ( P < .05). IPSLUAD outperformed other signatures in two independent cohorts. Conclusions: A robust immune‐related prognostic signature with great performances in multiple LUAD cohorts was developed in this study. Abstract : An immune‐related four‐gene prognostic signature was constructed using stability selection and penalized COX regression. Functional analysis suggested this signature was closely associated with innate immunity component. Our signature may server as a promising prognostic biomarker for LUAD in the future.